Que inter-relações entre géneros de texto e conhecimento gramatical podem ser objeto de conhecimento explícito e de avaliação? - Coutinho, Antónia (Revista da Associação Portuguesa de Linguística, 2019)
In this paper, we discuss epistemological and theoretical approaches of grammatical and textual contents, focusing on their relevance in learning (Portuguese) contexts. We will argue that different epistemological approaches can be used complementarily; however, clear objectives must lead to different assessment tasks, ensuring that they are not masking or merging the specific identity of texts, which can’t be reduced to linguistic objects, if we consider them in a social interactionism epistemological approach.